Hybrid decision technique for supplier selection - Tan, Keng Guan. (2010)
The aim of the hybrid decision technique for supplier allocation is to help corporate decision makers who are faced with making numerous and conflicting evaluations to decide on the choice of supplier for business collaboration, follow by recommending splitting order quantities obtained under the limitations from supplier such as capacity, procurement criteria and user‐specified constraints. There is an appeal for effective supplier‐selection as it helps corporation to build business competitive advantage and pull off strong attainment in interrelated corporate objective. Currently, the multiple criteria decision making techniques of cognitive advisor system that are implemented during previous final year projects could neither consider supplier capacities and constraints nor handle the order allocation. Hence, the project propose to develop a multiple objective programming model based on a multiple criteria decision making context to provide a systematic and rational approach for performing supplier‐selection and order splitting. To implement a dependable and viable technique, the author reviewed the use of Matlab optimization solvers, nonetheless ultimately developing a customized branch and bound algorithm for solving the devised model.